A Scoping Review of the Evidence on Health Promotion Interventions for Reducing Waterpipe Smoking: Implications for Practice - Gardner, Karen; Kearns, Rachael; Woodland, Lisa; Silveira, Mariela; Hua, Myna; Katz, Milena; Takas, Klara; McDonald, Julie (Frontiers in Public Health, 2018)
Background: Waterpipe tobacco smoking is a traditional method of tobacco use, especially in the Eastern Mediterranean Region (EMR), but its prevalence is growing worldwide, especially among young people. Although often perceived as less harmful than other methods of tobacco use because the smoke passes through water, accumulating evidence shows harmful effects and that some smokers become addicted. Interventions that deglamourise and denormalise use have been recommended but little is known about the range and impact of different health prevention and promotion interventions. Methods: A scoping review of literature was undertaken to explore the breadth of literature and assess the range and impact of community based health promotion interventions for waterpipe smoking. Searches were conducted in Medline, Embase, CINAHL, Psychinfo, and the Cochrane database of systematic reviews. Interventions were classified using a health promotion framework and data extracted on the aspects of prevention/promotion addressed; key strategies employed, evidence of effectiveness or impact on behavior change as well as barriers to implementation and perceived success factors. Results: Ten studies were included in the review. They include brief interventions to increase quit rates; community campaigns to raise awareness and increase knowledge; web based health education and skill development to increase perceived risks and intention to quit; as well as studies that evaluated product labeling and opportunities for policy interventions to create healthy environments. Conclusions: The evidence base is small but growing. Brief interventions for waterpipe users, community campaigns, and web based tailored information can modify perceptions of addiction and increase intentions to quit. Product labeling may be an effective policy tool to curb waterpipe smoking. A range of policy interventions have been identified but not evaluated.